Responses of Quality and Quantity Yield of Garden Thyme (Thymus vulgaris L.) to Foliar Application of Bio-stimulator Based on Amino Acids and Methanol - H Naghdi Badi; MR Labbafi; N Qavami; A Qaderi; V Abdossi; MR Agharebparast; A Mehrafarin (Institue of Medicinal Plants, ACECR, 2015)
Background: Now, the use of amino acids and methanol as a plant biostimulant is very interested for the increased secondary metabolites in medicinal plants. Objective: The aim was to evaluate the effect of biostimulants and methanol on the content and components of essential oil and morphological traits of thyme (Thymus vulgaris L.). Methods: This experiment was conducted on the basis of randomized complete block design with nine treatments and three replications. The treatments of this study included foliar application of kadostim, fosnutren, humiforte, and aminolforte, each of them with two levels of methanol aqueous solution at 10 and 20 %v/v, and control treatment (without application of plant biostimulants and methanol). Results: The results showed that were statistically significant the number of branches, stem diameter, shoot dry weight, thymol and carvacrol content at the 1% level, and the number of leaves per stem, plant height, essential oil content, and leaf dry weight at the 5% level. The maximum plant height, number of branches, number of leaves per stem, stem dry weight, leaf dry weight, and shoot dry weight in treatment of kadostim with 20% methanol, and the highest stem diameter, essential oil content, thymol, and carvacrol content in treatment of humiforte with 20% methanol were obtained. Conclusion: Application of kadostim and humiforte with 20% methanol enhanced the quantitative and qualitative yield of thyme. Therefore, the integrated application of biostimulants and methanol can be synchronized with reduce the use of some chemical fertilizers to the extent that it was leading to sustainable agriculture and reduction of environmental pollution.